Economic Dispatch Thermal Generator Using Modified Improved Particle Swarm Optimization - Andi Muhammad Ilyas; M. Natsir Rahman (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
Fuel cost of a thermal generator is its own load functions. In this research, Modified Improved Particle Swarm Optimization (MIPSO) is applied to calculate economic dispatch. Constriction Factor Approach (CFA) is used to modify IPSO algorithm because of the advantage to improve the ability of global searching and to avoid local minimum, so that the time needed to converge become faster. Simulation results achieved by using  MIPSO method at the time of peak load of of 9602 MW, obtained generation cost is Rp 7,366,912,798,34 per hour, while generation cost of real system is Rp. 7,724,012,070.30 per hour. From the simulation result can be concluded that MIPSO can reduce the generation cost of  500 kV Jawa Bali transmission system of Rp 357,099,271.96 per hour or equal to 4,64%.